SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN SANKSI KETERLAMBATAN PERIZINAN SANTRI DENGAN MENGGUNAKAN METODE AHP - Muhammad Misdram (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Decision Support System  For  Determining  Sanctions  DelayLicensing Pupils Method Using AHPThis study  uses  the title  Decision Support System  For  Determining  Sanctions  DelayLicensing  Pupils  Method Using  AHP.  Sanctions  are sanctions  are  moderate and  mild  categories. Determining sanctions on students to easily and according to UHPN.  Ahp method is a method of splitting  a  complex  or  complicated  problems  in the  unstructured  situation  into  its component parts.  incorporates  considerations  and  personal judgment  in a logical way  and  influenced  the imagination,  experience,  and  knowledge  to  develop  a  hierarchy  of  problems  based on logic, intuition  and  experience  to  give  consideration.  AHP  is a process  to identify,  understand  and provide an estimate of  the overall system  interaction.  AHP  calculation  results  are not  different from the  results of  the calculations  are  done manually,  it is intended  by  the outcome  CR  <0.1, then the  ratio of  the consistency  of  the  calculation  can  be accepted.  If  sebliknya  repeated  using even numbers.